Changes in the Phylogenetic Structure of Alpine Grassland Plant Communities on the Qinghai–Tibetan Plateau with Long-Term Nitrogen Deposition - Yongqi Liu; Hao Shen; Shikui Dong; Jiannan Xiao; Ran Zhang; Hui Zuo; Yuhao Zhang; Minghao Wu; Fengcai He; Chunhui Ma (Plants)
Nitrogen (N) deposition rates have notably increased around the world, especially in high-altitude regions like the Qinghai–Tibetan Plateau (QTP). We conducted a six-year comprehensive experiment to simulate nitrogen deposition in an alpine grassland area near Qinghai Lake. Four levels of nitrogen depositions, i.e., 0 (CK), 8 kg N ha−1year−1 (N1), 40 kg N ha−1year−1 (N2), and 72 kg N ha−1year−1 (N3), with three replicates for each N treatment, were tested annually in early May and early July, with the meticulous collection of plant and soil samples during the peak growth period from 15 July to 15 August. We used the null model to evaluate the impact of environmental filtration and interspecific competition on the dynamics of the plant community was assessed based on the level of discrete species affinities within the plant community by constructing a phylogenetic tree. The results showed that the environmental filter was the predominant driver for the change of community’s genealogical fabric. The N2 and N3 treatments increased the influence of soil factors on the change of plant community structure. Climatic factors played a crucial role on the change of plant community in the CK grassland area, while soil factors were dominant in the N1- and N3-treated grasslands.